2006
DOI: 10.1136/aim.24.4.149
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Auricular Acupuncture on Smoking Cessation May Not Depend on the Point Chosen – An Exploratory Meta-Analysis

Abstract: Introduction Auricular acupuncture is given as a treatment for drug dependence. Points are usually chosen on the assumption that the body is represented somatotopically in the ear, although there is no anatomical basis for this. In clinical trials, sham treatment is often given at points that are supposedly 'incorrect' for the condition, in the belief that they are inactive. The aim of this study was to explore whether there is any difference in the effectiveness of auricular acupuncture at 'correct' and 'inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…In smoking cessation, acupuncture suggested promise in earlier trials. [87][88][89] In a recent meta-analysis, 90 auricular acupuncture was found to be effective for smoking cessation, independently of the points used. However, a recently updated review 61,91 showed no consistent evidence that acupuncture is superior to no treatment.…”
Section: Acupuncture In Mental Health (Schnyer)mentioning
confidence: 99%
“…In smoking cessation, acupuncture suggested promise in earlier trials. [87][88][89] In a recent meta-analysis, 90 auricular acupuncture was found to be effective for smoking cessation, independently of the points used. However, a recently updated review 61,91 showed no consistent evidence that acupuncture is superior to no treatment.…”
Section: Acupuncture In Mental Health (Schnyer)mentioning
confidence: 99%
“…It is administered on the basis of positive evidence for pain-related conditions such as osteoarthritis of the knee [4][5][6] as well as postoperative and chemotherapy-induced nausea and vomiting [7,8]. Despite the lack of positive scientific evidence, it is also used for other conditions such as asthma [9] and smoking cessation [10]. But side effects, even severe ones like pneumothorax, cardiac tamponade, and infections can occur [11][12][13][14][15][16][17][18][19][20][21][22] and a patient should be informed about these.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, observations were made over three treatment sessions, and it is not known what changes may have occurred with longer term treatments. Another significant concern has been with the choice of sham points frequently used as controls in acupuncture research (White & Moody, 2006). If the sham points are themselves active points, then the comparison of outcomes between the "treatment" and "sham" groups may be inappropriate.…”
Section: Discussionmentioning
confidence: 99%